Effect of edible-bird's nest in Tris and Bioxcell extenders on bull semen cryopreservation - Yusop, Dayang Rakhmioktaleawatty (2016)
The aim of this study was to evaluate the effect of supplementing Tris (Tr) and Bioxcell (Bx) extenders with edible-bird’s nest (EBN) on the quality of bull sperm upon cryopreservation. A total of 12 semen samples were collected from mature bulls by electroejaculation. A total of 12 semen samples were collected from mature bulls by electroejaculation. The semen samples were evaluated both freshly and after cryopreservation for quality based on % sperm general and progressive motility (under a microscope), viability and abnormal morphology (using eosin-nigrosin stain). The fresh samples were then diluted and extended using the two extenders containing 0% (control), 0.03%, 0.06%, and 0.12% of EBN. Chilled at 4°C for 3 hours before packaged into 0.25 mL straws and frozen into liquid nitrogen (-196°C) for 48 hours. Results for both extenders revealed insignificant differences (P>0.05) in all parameters between the different EBN treatment groups and control. Although not significant, 0.12% EBN in both extenders showed the lowest % abnormality, close to the fresh sample reading. Moreover, Bx tended to show reduced % abnormality than Tr for the same EBN treatments, implying more protective role played. In conclusion, EBN concentrations used in this study do not significantly improve sperm quality after freezing. Further research should be carried out with increased sample size and dosage of EBN in order to clarify the minimal improvement observed for parameters such as sperm abnormality.